2019
DOI: 10.1038/s41433-019-0608-7
|View full text |Cite
|
Sign up to set email alerts
|

A new era for giant cell arteritis

Abstract: The landscape of the investigation and management of giant cell arteritis (GCA) is advancing. In this review we will outline the recent advances by searching the current English literature for relevant articles using key words of giant cell arteritis, temporal arteritis, Horton's disease, investigation, and treatment. Delay in diagnosis, diagnostic uncertainty and glucocorticoid (GC) morbidity are among the highest concerns of clinicians and patients in this disease area. The positive news is that fast track p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 102 publications
1
118
0
4
Order By: Relevance
“…Skip lesions can be seen in 12% to 28% of the cases 123,125 . Features of healed arteritis have been described in literature but the findings are similar to histopathological changes in atherosclerosis 105,126,127 . Salvarani et al reported that vasa vasorum and periadventitial small vessel vasculitis should be considered as histopathological changes of GCA 128 .…”
Section: Investigationsmentioning
confidence: 89%
See 1 more Smart Citation
“…Skip lesions can be seen in 12% to 28% of the cases 123,125 . Features of healed arteritis have been described in literature but the findings are similar to histopathological changes in atherosclerosis 105,126,127 . Salvarani et al reported that vasa vasorum and periadventitial small vessel vasculitis should be considered as histopathological changes of GCA 128 .…”
Section: Investigationsmentioning
confidence: 89%
“…Cross-sectional view of temporal artery showing florid granulomatous inflammation and vaso-occlusion described in literature but the findings are similar to histopathological changes in atherosclerosis. 105,126,127 Salvarani et al reported that vasa vasorum and periadventitial small vessel vasculitis should be considered as histopathological changes of GCA. 128 This observation has been supported by Belilos et al 129 The significance of isolated vasa vasorum and periadventitial small vessel vasculitis in TAB specimens in the absence of arterial involvement is uncertain.…”
Section: F I G U R E 3 Temporal Artery Biopsy F I G U R Ementioning
confidence: 99%
“…The early diagnosis of large vessel vasculitis is crucial to prevent serious irreversible complications [6 , 10 , 11] . It is also important in the prevention of toxicity from unnecessary drug management [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Painless loss of vision is an atypical presentation for temporal arteritis. Temporal arteritis patients who suffer visual deficits in one eye have a higher risk (20-50%) of bilateral vision loss if they are not treated with or discontinue their immunosuppressant treatment [10 , 11] .…”
Section: Discussionmentioning
confidence: 99%
“…naime, cvi se opisuje kao dio kliničke slike Gca, iako vremenski odmak od više godina se u ovom slučaju ne bi uklopio u kliničku sliku Gca. obzirom da bolesnici s neprepoznatim Gca često "lutaju" između neurologa, oftalmologa, infektologa i reumatologa, početak terapije glukokortikoidima u kliničkoj praksi nije pravovremen (20,21), što može dovesti do trajnog gubitka vida i ostalih ozbiljnih komplikacija ove bolesti kao što je bio slučaj i u naše bolesnice.…”
Section: Bajo D I Sur Gigantocelularni Arteritis S Oteklinom Parotidnih žLijezdaunclassified